2020
DOI: 10.1158/1078-0432.ccr-19-3416
|View full text |Cite
|
Sign up to set email alerts
|

The Immunosuppressive Niche of Soft-Tissue Sarcomas is Sustained by Tumor-Associated Macrophages and Characterized by Intratumoral Tertiary Lymphoid Structures

Abstract: Translational Relevance Treatment paradigm for sarcomas has been unchanged for the past four decades with survival outcomes plateauing and patients with HR disease facing an abysmal prognosis. SARC028, trial testing pembrolizumab in STS, demonstrated responses in UPS and dedifferentiated liposarcomas. Alliance A091401, trial combining ipilimumab and nivolumab, showed responses in more histologies, but OS rates similar to standard chemotherapy. Here, we compare the immune TME of two molecularly distinct sarcoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…First, the immune microenvironment is largely independent of tumor type. Previous studies have shown that immune cell accumulation is associated with diverse sarcoma subtypes, where dominant infiltration of TAMs was observed in UUS and undifferentiated pleomorphic sarcomas (29,30). In line with these reports, our results indicate that the immune microenvironment depends on factors other than the tumor type.…”
Section: Discussionsupporting
confidence: 91%
“…First, the immune microenvironment is largely independent of tumor type. Previous studies have shown that immune cell accumulation is associated with diverse sarcoma subtypes, where dominant infiltration of TAMs was observed in UUS and undifferentiated pleomorphic sarcomas (29,30). In line with these reports, our results indicate that the immune microenvironment depends on factors other than the tumor type.…”
Section: Discussionsupporting
confidence: 91%
“…Using single-cell RNA sequencing and mass cytometric profiling, we profile tumor-infiltrating immune cells from transplant and primary tumors before and after RT and anti-PD-1 immunotherapy, which reveals marked differences in their immune landscapes. We show that transplant, but not primary, tumors are enriched for activated CD8+ T cells and PD-L1+ macrophages, which are present in human sarcomas that respond to PD-1 blockade 20,21 . These results suggest that patients with a sarcoma immune phenotype similar to transplant tumors may benefit most from PD-1 blockade and radiotherapy.…”
mentioning
confidence: 83%
“…In addition, other gene signatures containing 8 and 19 genes related to the presence of T follicular helper cells, type 1 helper CD4 + T cells and B cells were reported in breast 54 and gastric 55 cancers. Collectively, this has led to the detection of TLS in lung, 41 , 45 , 56 , 57 oral squamous cell carcinoma, 58 breast, 54 , 59–61 colon, 51 , 62 stomach, 55 , 63 , 64 liver, 65 sarcoma, 3 , 66 , 67 bladder, 68 clear cell renal cell carcinoma, 4 ovarian cancer 46 , 69 and melanoma 4 , 5 , 15 , 44 , 50 , 70 ( Table 1 ). TLS formation and densities vary between tumor types, and between patients.…”
Section: Tertiary Lymphoid Structures In Cancer – Prognostic and Predmentioning
confidence: 99%